Addressing the Notions of Reality, Representation and Relevance in Manipur State History Textbooks - Subba, Manisha (JOURNAL OF INDIAN EDUCATION, 2013)
In our education system, the textbook is an important aspect through which the curriculum is selected and organised. History being a dynamic subject has varying interpretations and representations. It provides us with the platform to see whether the representation is complete and question the relevance of the texts with so many realities co-existing. In this research paper, the researcher tried to construct the reality with the help of secondary sources, and then compare the representation as given in the History textbooks. The attempt to understand the relevance of textbooks was done by problematising it and studying the social conditions on the basis of which the content is selected and organised.